Beliefs and Consumer Search in a Vertical Industry. Issue 5 (11th September 2019) - Janssen, Maarten; Shelegia, Sandro
Abstract: This paper studies vertical relations in a search market. As the wholesale arrangement between a manufacturer and its retailers is typically unobserved by consumers, their beliefs about who is to be blamed for a price deviation play a crucial role in determining wholesale and retail prices. The common assumption in the consumer search literature is that consumers exclusively blame an individual retailer for a price deviation. We show that in the vertical relations context, predictions based on this assumption are not robust in the sense that if consumers hold the upstream manufacturer at least partially responsible for the deviation, equilibrium predictions are qualitatively different. For robust beliefs, the vertical model can explain a variety of observations, such as retail price rigidity (or, alternatively, low cost pass-through), nonmonotonicity of retail prices in search costs, and (seemingly) collusive retail behavior. The model can be used to study a monopoly online platform that sells access to final consumers.